2014
DOI: 10.1051/shsconf/20141201065
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Perceived Importance and Performance of Penang Island Attributes

Abstract: Abstract. This paper examines the gender differences in perceived importance and performance of Penang Island attributes. The data was drawn from questionnaire survey of 801 international tourists who visited the island between August and November 2012. Previous studies related to gender differences in Malaysian destinations are found scarce and neglected, thus this paper aims to bridge this knowledge gap. The needs to study gender differences are related to the suggestions that men and women engage in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several studies suggest that women tend to show a preference for engaging in leisure activities, dancing, visiting relatives, and shopping (Carr, 2001;Deem, 1986;Mieckzowski, 1990). The identification of such widespread gendered tourist preferences suggests that understanding gendered tourist engagement and loyalty might be becoming increasingly important (Omar, Abooali, Mohamed, & Mohamad, 2014;Salazar, 2012).…”
Section: Gender Differences In Tourist Engagement and Loyaltymentioning
confidence: 99%
“…Several studies suggest that women tend to show a preference for engaging in leisure activities, dancing, visiting relatives, and shopping (Carr, 2001;Deem, 1986;Mieckzowski, 1990). The identification of such widespread gendered tourist preferences suggests that understanding gendered tourist engagement and loyalty might be becoming increasingly important (Omar, Abooali, Mohamed, & Mohamad, 2014;Salazar, 2012).…”
Section: Gender Differences In Tourist Engagement and Loyaltymentioning
confidence: 99%
“…A number of studies have addressed gender differences in leisure activities (Jönsson & Devonish, 2008;Lin, Wong, & Ho, 2015;Omar, Abooali, Mohamed & Mohamad, 2014;Richter & Theobald, 1995;Ryan, Henley, & Soutar, 1998;Zhou, 2010). However, most focus on the experiences of western tourists: there are few studies on Asian tourists despite the size of the market.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ariffin and Maghzi [67] found modifications in the satisfaction of tourists staying in hotels depending on the sex of the tourist, whereby men might choose other types of accommodation due to their higher expectations. Omar and collaborators showed that women give more importance to accommodation services when choosing a destination than men do [68], although a study of kayaking tourists in Poland showed that men place greater importance on accommodation than women [69]. Other research focusing on Spanish sports tourists found differences in distributions according to the type of accommodation chosen when analyzing gender [70].…”
Section: Discussionmentioning
confidence: 99%